The Past of a Future: a characterization of Cipriano Salcedo, protagonist of "El hereje", by Miguel Delibes (XXI Century. Spanish Literature and Culture, 2004)
Lutheranism, a divided society and the recuperation of the so called ‘historic memory’ can allact as an underlying axis for the main character of Delibes’ novel, El hereje, creating a man whose life ismarked by his orphanhood, which unleashes the hate his father feels for him, and the unrequited love forhis nursemaid. At his adulthood, trade, marriage and a series of decisions move him to take part in a sectwhich follows the protestant currents that are secretly penetrating that Spain at the time and which, intime, will cause his death.
Keywords: Delibes; El hereje; Characteristics; main character